Factors Influencing the Purchase Intention of Pop Mart Products: Evidence from Filipino Consumers in Metro Manila, Philippines - Benedict G. Leones; Micaella M. Keyda; John Christopher C. Jalgalado; Maria Kristina Samantha D. Ipia; Sheryl Antonette Lozano; Jayvie O. Guballo (Journal of Management Studies and Development, 2026)
This study examines the factors influencing the intention to purchase among Filipino consumers toward Pop Mart products using a predictive-correlational research design. 383 Pop Mart customers in Metro Manila took part in both online and on-site surveys. The data were analyzed using statistical tools such as weighted mean, frequency and percentage distribution, and multiple linear regression analysis. The findings revealed that Attitude towards Behaviour, Perceived Value, and Word-of-Mouth had a significant influence on purchase intention among Filipino consumers when buying Pop Mart products, whereas Uncertainty did not. This study would greatly help marketers, brand managers, and even business owners who are aiming to enhance their purchase intention among their target markets like young Filipino consumers. Despite knowing that attitude, perceived value, and word-of-mouth significantly influenced intention to purchase, similar brands like Pop Mart may develop a strategy that highlights emotional satisfaction beyond owning the collectibles, uniqueness of the product, and the power of social influence that drives purchase intention.